Antimalarial properties of crude extracts of seeds of Brucea antidysenterica and leaves of Ocimum lamiifolium. Issue 1 (December 2016) - Kefe, Atetetgeb; Giday, Mirutse; Mamo, Hassen; Erko, Berhanu
Abstract Background The search for new antimalarial drugs has become increasingly urgent due to plasmodial resistance to existing drugs. As part of this global effort, the present study aimed at evaluating the antimalarial activity of two traditionally used medicinal plants against the disease. Methods Acute toxicity and four-day suppressive effects of aqueous, methanol and chloroform extracts of the seed and leaf ofBrucea antidysenterica andOcimum lamiifolium, respectively, were investigated in Swiss albino mice usingPlasmodium berghei using standard procedures. Results Methanol extract of the leaves ofO. lamiifolium did not exhibit any sign of acute toxicity up to the dose of 2000 mg/kg body weight. However, all mice provided with seeds ofB. antidesenterica at a dose of 2000 mg/kg body died within 24 h. The aqueous, methanol and chloroform crude extracts ofB. antidesenterica significantly (p  < 0.05) inhibited parasitaemia in a dose-dependent manner and prevented body weight loss at doses of 200, 400 and 600 mg/kg body weight. In addition, the extracts prolonged the mean survival time ofP. berghei -infected mice compared to the non-treated control. However, it did not prevent reduction in packed cell volume except the chloroform extract in three doses and methanol extract at 200 mg/kg and 400 mg/kg. Extracts fromO. lamiifolium also exhibited significant (p  < 0.05) antiplasmodial activities. The extracts did not prevent body weight loss and PCV reduction, especially in chloroform. The highest suppression was recorded from aqueous crude extract ofO. lamiifolium with 35.53 % in the dose of 600 mg/kg. On the other hand, a similar higher suppression was found in both methanol and chloroform of crude extracts ofB. antidesenterica with 47.70 %, 46.44 % of chemosuppression, respectively, in its highest dose tested. Conclusion Crude aqueous, methanol and chloroform extracts of the two medicinal plants possess acceptable antimalarial effects. However, further investigation should be pursued on toxicity study and to isolate the bioactive components responsible for the observed antimalarial action of the plants.